Research of Space Network Node Route Planning and Localization in HAPS Space - Liu, 2Xiaoyang; Liu, Hengyang; Liu, Chao (Discoveries in Agriculture and Food Sciences, 2018)
Compared with the traditional method of detection tracking, space sensor networks(WSN) for its good character of the traditional tracking methods inadequate. For the localization algorithm and route planning of space sensor network exists a big positioning error in high altitude platform station (HAPS) space communication. Space sensor network communication system is researched. According to the anchor nodes and unknown nodes, location algorithm and node route planning method of WSN are proposed in this paper. The performance of the node density and location error are simulated and analyzed in HAPS. The simulation results show that the performance of proposed location error is better than the traditional algorithms.